Emergency department overcrowding: first Swiss application of the Emergency Department Work Index and risk factors for overcrowding - Herzog, Aline; Luster, Michael; Keller Lang, Dagmar I.; Slankamenac, Ksenija (Frontiers in Public Health, 2025)
IntroductionEmergency department (ED) overcrowding is associated with increased waiting time, reduced patient satisfaction, and decreased quality of care. Numerous validated scores are available for assessing ED overcrowding. The Emergency Department Work Index (EDWIN) is the most established score for quantifying ED overcrowding. We assessed the applicability of the EDWIN in a Swiss ED and investigated further predictors of ED overcrowding.MethodsIn this retrospective analysis, we included consecutive ED visits at a tertiary care hospital between 1st December and 31st December 2016. The median EDWIN per hour was defined as the first endpoint. To investigate predictors of overcrowding, we grouped ED visits with an EDWIN ≤2 as not overcrowded and those with an EDWIN >2 as overcrowded and performed multivariable regression analysis.ResultsThe median EDWIN score per hour was 1.4 (IQR 1.0–1.9). In 394 calculations (53%), the ED was active; 189 calculations (25.4%) showed a very busy ED; and in 161 observations (21.6%), the ED was severely overcrowded. On average, the ED was severely overcrowded six times per day. The highest EDWIN score was reported on Saturdays [mean 2.1 (SD 1.2)] and Sundays [mean 1.7 (SD 1.0)]. During weekends, overcrowding occurred from 8 p.m. to 05 a.m., and the EDWIN score ranged from 2.2 to 3.1. During the week, the mean EDWIN score ranged from 1.3 to 1.6. A reduced number of emergency physicians during night shifts (p < 0.001), an increased number of patients in the ED treatment area (p < 0.001), patients waiting for admission to the ward (p < 0.001), weekend periods (p = 0.001), and a higher number of isolated ED patients due to infections (p < 0.001) showed a highly significant association with overcrowding. In the case of overcrowding, the waiting time was prolonged (p = 0.034).ConclusionThe EDWIN score was easily applicable in a tertiary care Swiss ED, objectively displayed severe overcrowding during weekend nights, and was strongly associated with the number of available attending emergency physicians, the number of patients in the ED treatment area, patients waiting for admission to the ward, weekend periods, and the number of patient isolations.